Phosphatase Enzymes in Soils: Nature and Location of the Enzymes and Phosphorus Immobilization and Mineralization - ADEBAYO, ADEWALE (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The nature and location of phosphatase enzymes produced by soil microorganisms under different copping and ecological conditions were evaluated by incubating the supernatant of a 1:10 soil-distilled water suspension for 40 weeks in microbial P-surplus and P- deficient conditions. At various time intervals, the cell-free, cell-bound, total dissolved P, dissolved inorganic P and turbidity of the cultures were determined. Results indicated that most of the phosphatase enzymes existed in a cell-bound rather than cell-free state irrespective of the P status of the medium during the first 8 weeks of incubation. Total phosphatase activity showed little tendency to decline with continued incubation. However, in all the systems the rate and extent of organic P mineralization varied but was not related to phosphatase activity. Phosphatase activity was also not related to the living biomass in these cultures